2021
DOI: 10.1155/2021/6670834
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of Interleukin-2 Receptor Subunit Gamma Reveals Poor Prognosis in Human Gastric Cancer

Abstract: Precision medicine for gastric cancer (GC) is still an unsolved issue, because most available target drugs are not specifically designed for GC. Exploring novel signaling molecules with target value for GC is in urgent need. This study aimed to reveal that interleukin-2 receptor subunit gamma (IL2RG) is such a key molecule in human GC progression. GC tissues and paracancerous gastric tissues were collected from 7 patients (5 males and 2 females) during tumor radical excision surgery. These tissues were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…As one of the most common tumors with a high morbidity and mortality, gastric cancer (GC) leads to a poor prognosis and increases critical social burden with 5.7% incidence and 8.2% mortality rates ( Bray et al, 2018 ). More than 50% of diagnosed GC patients were at advanced stages and the prognosis of GC was relatively poor with only less than 30% overall 5-year survival rate ( Yang et al, 2020a ; Wang et al, 2021 ). Despite remarkable progress have been made for the treatment of GC, including radiotherapy, chemotherapy and surgery according to different locations and clinical stages, there is still lack of effective strategies for the advanced GC treatment ( Ai and Wang, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most common tumors with a high morbidity and mortality, gastric cancer (GC) leads to a poor prognosis and increases critical social burden with 5.7% incidence and 8.2% mortality rates ( Bray et al, 2018 ). More than 50% of diagnosed GC patients were at advanced stages and the prognosis of GC was relatively poor with only less than 30% overall 5-year survival rate ( Yang et al, 2020a ; Wang et al, 2021 ). Despite remarkable progress have been made for the treatment of GC, including radiotherapy, chemotherapy and surgery according to different locations and clinical stages, there is still lack of effective strategies for the advanced GC treatment ( Ai and Wang, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A separate investigation disclosed the upregulation of IL-2RG in gastric cancer (GC) tissues, with high IL-2RG levels predicting a poorer OS. This suggests that IL-2RG may indeed have a role in developing human GC [ 21 , 22 ]. These collective findings, consistent with our results, reinforce the significance of IL-2RG in cancer biology.…”
Section: Discussionmentioning
confidence: 99%
“…IL-2RG influences malignant cell differentiation, activation, and proliferation, shaping the TME [ 20 ]. Particularly, IL-2RG expression has been identified in human gastric carcinomas and is associated with an unfavorable prognosis [ 21 , 22 ]. In recent years, the study of miRNAs in cancer research has gained significant attention due to their involvement in various biological processes, including carcinogenesis [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Jia et al [ 28 ] reported that CA19-9 and CEA may also be used as predictors of efficacy and progression-free survival for the CET + FOLFOX4 regimen in patients with advanced colorectal cancer. Moreover, changes in the inflammatory microenvironment are strongly linked to tumorigenesis and progression, of which pro-inflammatory IL-2 may be related to GC progression and poor prognosis, whereas the deficiency of anti-inflammatory factor IL-10 may be related to Helicobacter pylori infection + chronic alcohol-induced GC[ 29 , 30 ]. This study measured inflammation markers, IL-2 and IL-10.…”
Section: Discussionmentioning
confidence: 99%